1993
DOI: 10.1007/bf01518451
|View full text |Cite
|
Sign up to set email alerts
|

Epitope specificity of the anti-(B cell lymphoma) monoclonal antibody, LL2

Abstract: LL2 is a murine monoclonal antibody IgG2a reactive with B cells and non-Hodgkin's B-cell lymphoma, which, in a radioiodinated form, induces responses in lymphoma patients [Goldenberg et al. (1991) J Clin Oncol 9:548-564]. In this report we identify LL2 as a member of the CD22 cluster. The molecular size of the antigen, its expression profile, and competitive blocking studies were used to establish this identification. By Western blot analysis and immunoprecipitation studies using the Raji Burkitt's lymphoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…In vitro cytotoxicity of LL2-onconase: duration of exposure LL2 is known to be rapidly internalized 4 and our experiments have shown that more than 95% of the antibody is specifically bound to the cell surface by 2 hours (data not shown). To determine whether a short-term exposure to the conjugate would be sufficient to cause cytotoxicity, inhibition of protein synthesis was examined in an experiment that compared the effects of LL2-onconase on Daudi cells after a 1-hour treatment compared with continuous exposure of Daudi cells to the conjugate ( Figure 5).…”
Section: Characterization Of Onconase Conjugated To Ll2mentioning
confidence: 78%
See 2 more Smart Citations
“…In vitro cytotoxicity of LL2-onconase: duration of exposure LL2 is known to be rapidly internalized 4 and our experiments have shown that more than 95% of the antibody is specifically bound to the cell surface by 2 hours (data not shown). To determine whether a short-term exposure to the conjugate would be sufficient to cause cytotoxicity, inhibition of protein synthesis was examined in an experiment that compared the effects of LL2-onconase on Daudi cells after a 1-hour treatment compared with continuous exposure of Daudi cells to the conjugate ( Figure 5).…”
Section: Characterization Of Onconase Conjugated To Ll2mentioning
confidence: 78%
“…LL2 has a highly restricted specificity; it does not cross-react with peripheral blood cells, including the blood's normal B cells, yet is reactive with virtually all cases of NHL. 4 Recently, preliminary results of a clinical trial in which the humanized version of LL2, Epratuzumab, was used have been reported. 5 No dose-limiting toxicity nor human antiEpratuzumab antibody response was observed at the highest dose administered (1000 mg/m 2 per week), whereas objective responses were noted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the published data showing that RFB4, the parental IgG of HA22, competed partially with another mAb that binds to domain 3. 17 The two new antibodies reacted only to the region including domains 5 to 7 (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
“…Several anti-CD22 monoclonal antibodies have been developed, with immunoprecipitation studies demonstrating that they react to different Ig domains. Epratuzumab, a humanized anti-CD22 antibody, which is the subject of this review, and the RFB4 antibody compete for binding to the third Ig domain (Stein et al, 1993).…”
Section: Cd22 As a Target For Immunotherapy In B-cell Malignanciesmentioning
confidence: 99%